Pemanfaatan Kayu Kelapa Sebagai Bahan Pembuatan Kitchen Set - Adi Santosa, Iwan Kristantama Wijaya (Intra, 2014)
Failure which usually found in the designer in processing coconut wood is because they lack an understanding of the characteristics of the wood. Some characteristics of the wood is its density doubled from wood in general, great depreciation, and easily weathered by water. Departing from these characteristics, then it conducted construction and finishing experiment to optimize the coconut wood which identical to the wet area. The method which applied is experimental research method. For table top part, shells and resin materials will be the subject of experiment to determine whether they can be table top material. The data from these experiments will be used for reference in designing a kitchen set. From the experiments that have been done, then the most appropriate finishing for coconut wood which be used for a kitchen set is polyurethane. Construction for coconut wood which the most suitable on the use of a kitchen cabinet set is dowel construction. The system which is suitable for the application of coconut wood when used as a kitchen setâs cabinet is frame system (framework or brim). Coconut wood needs to be combined with other material with a lighter character and stabilized. Materials shells and resin easily scratched so it canât be used as table top. Therefore, the table top material used for this kitchen set design is an conventional material. Once analyzed, stainless steel and solid surface material is recommended.